Efeitos da urbanização e do desenvolvimento agrícola sobre a estrutura das diatomáceas perifíticas de córregos tropicais. - Moresco, Carina (2011)
Due to the growing world population, the urbanization process is accelerated, as well as farming practices. Thus, rivers and streams are subject to changes in its physical and chemical characteristics, causing negative effects on organisms of these ecosystems. This study aimed to evaluate spatial and temporal variations in the structure of the periphytic diatom assemblages in streams affected by urban and rural areas of the city of Maringá, PR, relating them to abiotic variables. Indicator species were also selected (IndVal). The results of this study were divided into two chapters, the first entitled "Changes in the structure of the periphytic diatom assemblages in tropical streams under the influence of rural and urban impacts." To prepare this, data from an urban stream and a stream of rural were used. Differentiation of periphytic diatom assemblages among streams was evident (Main Effects ANOVA, p≤0.05, NMS, stress13.73, p = 0.009). The variables with greatest influence on assemblage structure of periphytic diatoms were total nitrogen (TN), electrical conductivity, dissolved oxygen (DO), chemical oxygen demand (COD), biochemical oxygen demand (BOD5) and flow (Procrustes, m2 = 0.7607 and p = 0.0001). In the second chapter entitled "Effects of urbanization and agriculture on the structure of the periphytic diatom assemblage in a tropical stream", were used data from a stream whose watershed has urban and rural influences. The longitudinal gradient of the stream was evaluated and this differed between the headwater assembly, the intermediate section and the mouth. There was greater similarity between the intermediate section and mouth when compared to headwader. (NMS - stress = 10.82, p = 0.009). The abiotic variables that had the greatest influence on the distribution of the periphytic diatom assemblages among the stretches of the stream were orthophosphate (PO4), pH, dissolved oxygen (DO), total nitrogen (TN) and flow velocity (Procrustes, m2 = 0.6921 and p = 0.0001). In both studies the spatial variability was more important than the temporal, suggesting that land use was more important in structuring the assembly of periphytic diatoms than seasonal variation of abiotic factors.